1999
DOI: 10.1161/01.res.85.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Reactive Oxygen Species and Cholesterol on Endothelial Nitric Oxide Synthase and Endothelial Cell Caveolae

Abstract: Abstract-Synthesis of nitric oxide (NO) by endothelial nitric oxide synthase (eNOS) is critical for normal vascular homeostasis. eNOS function is rapidly regulated by agonists and blood flow and chronically by factors that regulate mRNA stability and gene transcription. Recently, localization of eNOS to specialized plasma membrane invaginations termed caveolae has been proposed to be required for maximal eNOS activity. Because caveolae are highly enriched in cholesterol, and hypercholesterolemia is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 47 publications
4
85
0
1
Order By: Relevance
“…Cell Culture-Bovine aortic endothelial cells (BAEC) were purchased from Clonetics (San Diego, CA) and were cultured in medium 199 supplemented with 10% fetal bovine serum (Invitrogen), basal MEM vitamins, and amino acids (Invitrogen) as described before (29). Confluent cells cultured in 60-mm dishes were serum-starved for 18 - Immunoblot Analysis-Western blot analyses were performed as described previously (24,31).…”
Section: Methodsmentioning
confidence: 99%
“…Cell Culture-Bovine aortic endothelial cells (BAEC) were purchased from Clonetics (San Diego, CA) and were cultured in medium 199 supplemented with 10% fetal bovine serum (Invitrogen), basal MEM vitamins, and amino acids (Invitrogen) as described before (29). Confluent cells cultured in 60-mm dishes were serum-starved for 18 - Immunoblot Analysis-Western blot analyses were performed as described previously (24,31).…”
Section: Methodsmentioning
confidence: 99%
“…In line with these findings, the data of the present study revealed that the stimulation of endothelial cells with pro-inflammatory or pro-atherogenic stimuli reduced the S-nitrosylation of distinct proteins in endothelial cells and specifically reduced the Snitrosylation of the p17 subunit of caspase-3. The decline of S-nitrosylation could be due to an inhibition of eNOS expression and/or NO bioavailability induced by TNF␣-mediated eNOS mRNA destabilization (27) or increased oxidative stress (30,31). However, pharmacological inhibition of NO synthesis for 18 h with L-arginine-L-NAME or L-NMMA did not decrease the S-NO levels, although control experiments confirmed the inhibition of eNOS (data not shown).…”
Section: Figmentioning
confidence: 96%
“…58 Evidence exists that ROS induce endothelial dysfunction by affecting eNOS expression or by inactivation of NO through the formation of lipid peroxidation products and peroxynitrite radicals that disturb directly the EC membrane. [61][62][63] In ECs, the enzymatic systems that contribute to the increase production of ROS are xanthine oxidase, NADH/ NAD(P)H oxidase, and eNOS. Within the atherosclerotic plaque, the inflammatory cells and SMCs are a source of superoxide possibly via angiotensin II-activated NAD(P)H oxidase.…”
Section: Oxidative Stress-induced Ec Dysfunctionmentioning
confidence: 99%